GUIDELINES FOR DEVELOPING THE LEADERSHIP BEHAVIOR OF THE SCHOOL ADMINISTRATORS AFFECTING THE EFFECTIVENESS OF SCHOOLS UNDER MAHASARAKHAM PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Sukabut , Surawoot; Chansirisira, Pacharawit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this study were : 1) to examine the leadership behavior of school administrators, 2) study at effectiveness of schools, 3) to find out a relation between the leadership behavior of school administrators and effectiveness of schools and 4) to develop guidelines for developing the leadership behavior of school administrators affecting the effectiveness of schools under Mahasarakham Primary Educational Service Area Office 1 2. The research method was divided into 2 phases. The first phase studied current conditions and a relation between the leadership behavior of school administrators and effectiveness of schools. The samples were 291 teachers. The research tools was a rating scale questionnaire. The second phase was a developing guideline to encouraged the leadership behavior of school administrators affecting the effectiveness of schools. The development guideline was evaluated by 5 experts, selected from purposive sampling technique. The research tools were used in the study were an interview from and appropriateness and feasibility of the guideline. Percentage, mean, standard deviation and a relation between the leadership behavior of school administrators and effectiveness of schools synthesis by Pearson’s Product Moment Correlation Coefficient were the parameters used for statistical analysis. The results indicates that:1)The overall of leadership behavior in school administrators under Mahasarakham Primary Educational Service Area Office 1 was found to be at the high level as follow : the productivity attentive behavior, the relationship attentive behavior and team working attentive behavior.2) The overall of the effectiveness in schools under Mahasarakham Primary Educational Service Area Office 1 was found to be at the high level as followed : The ability to develop students to get high learning achievement, The ability to develop students to be positive attitude, the efficiency in modification and development schools and the efficiency in solving school problems.3) The relationship between the leadership behavior of school administrators and effectiveness of schools was statistically significant at .01 level.4)guidelines for developing the leadership behavior of school administrators affecting the effectiveness of schools under Mahasarakham Primary Educational Service Area Office 1 can be include 3 parts ; 1) the 7 guidelines of productivity attentive behavior part and 2) The 4 guidelines team working attentive behavior part All 11 guidelines were appropriateness and feasibility of the guidelines at the high level.